Analysis of the gains and losses of ecosystem service value under land use change and zoning in Qiqihar - Zuo, Zhiqian; Yang, Yanzhao; Wang, Ran; Li, Jinxiao; Zhang, Pengtao (Frontiers in Ecology and Evolution, 2023)
The gains and losses of the ecosystem service value (ESV) of Qiqihar City from the perspective of the city and county level is essential to grasp the land use change and its impact on ESV. In this paper, the analysis was based on the land use data and natural socioeconomic data of Qiqihar in 2010 and 2020. On this basis, the ecosystem service assessment model, flow analysis model, 2D graph cluster, and other methods were adopted. Then, the city was divided into ecological functional zones from the county level. The results showed as follows. 1) The land use change of Qiqihar was obvious in the past decade. The area of cultivated land, wetland, construction land, and other land increased, while that of woodland, grassland, and water decreased. The changed land area accounted for 30.95% of the total area under the jurisdiction. 2) The ESV of Qiqihar increased by 869 million yuan, and the change rate of the total value was 2.47%. The total value of cultivated land and wetland accounted for more than 70.0% of the total value of ecosystem services in the two phases. It was the main source of the ESV of Qiqihar. 3) The conversion of land use types was not all conducive to the increase of ESV. It mainly came from the conversion of cultivated land and grassland ecosystems to wetland ecosystems. The increase was 20.75% and 19.68%, respectively, a total of about 5.256 billion yuan. Woodland, water, and wetland converted to other land types, which led to ESV losses. The largest loss was the conversion of wetland to cultivated land, about 3.338 billion yuan. 4) The 16 counties, cities, and districts of Qiqihar were divided into three ESV zones according to the correlation of nine ESV indicators per unit area: the central wetland ecological conservation zone, the western characteristic agriculture and point-shaped wetland ecological functional zone, and the northeast agricultural ecological environment construction zone. Corresponding land use strategies were provided as a theoretical basis and reference for ecological construction.